Sensitivity and specificity of diagnosis of interproximal caries by last-year dental students - Farzaneh Shirani; Aseieh Zamaninaser; Farzaneh Mosavat; Mehdi Hamzeh (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: The aim of this study was to evaluate the specificity and sensitivity of last-year dental students' diagnostic skills for proximal caries on bitewing radiographs in Isfahan Faculty of Dentistry.Materials and methods: In this study, 50 intact and carious molar and premolar teeth were mounted in wax and underwent bitewing radiographic techniques. Then 40 volunteer dental students from Isfahan Faculty of Dentistry categorized proximal carious lesions in special questionnaires. Subsequently the teeth were sectioned in a mesiodistal direction at the center of the contact area and evaluated clinically under a microscope at ×5. The results reported by the students were compared with the results of microscopic evaluation (gold standard). Statistical formulas were used to determine specificity, sensitivity and false positive and negative results. Results: This study showed that sensitivity of intact and carious surfaces were 64.8% and 62.2%, respectively. Furthermore, sensitivity of enamel and dentin caries were 55.6% and 69.6%, respectively.Conclusion: The results showed that last-year dental students had a high rate of incorrect diagnosis in comparison with the gold standard. Therefore, more attention should be paid to instructing dental students. Key words: Bitewing radiography, Caries, Dental student, Proximal caries, sensitivity, specificity.